1988
DOI: 10.1063/1.454710
|View full text |Cite
|
Sign up to set email alerts
|

The negative ion states of sulfur hexafluoride

Abstract: The reaction of SF6 with thermal electrons has been studied in a Ni-63 atmospheric pressure ionization source for a quadrupole mass spectrometer (API/MS). The major ions that are observed are the parent negative ion (SF−6) and the parent minus a fluorine atom (SF−5). The ratio of [SF−5]/[SF−6] is highly temperature dependent above 500 K. The dissociation energy of the ground state negative ion into SF−5 and F has been determined to be 1.35±0.1 eV. This gives values of 3.8±0.15 eV for the electron affinity of S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 58 publications
4
37
0
Order By: Relevance
“…The C6F14 used in commercial applications is generally a mixture of approximately 85% n-C6F14 with the remainder composed of various branched C6F14 isomers. SF 6 has been the subject of numerous electron attachment studies, and several authors have compared previous work [Chen et al, 1988;Christophorou, 1984;Petrovic and Crompton, 1985;Smith et al, 1984]. SF 6 is a fast attacher producing mainly (>99%) SF•-at 300 K, with a minor dissociative pathway forming SF•-+ F. Only the minor (i.e., slow) dissociative attachment pathway was considered in the study by Ravishankara et al [1993], and in the present treatment we assume that SF 6 is destroyed at the overall (fast) attachment rate in order to maximize the effects of electrons and arrive at a lifetime lower limit; this is discussed Table 1.…”
Section: Electronsmentioning
confidence: 73%
“…The C6F14 used in commercial applications is generally a mixture of approximately 85% n-C6F14 with the remainder composed of various branched C6F14 isomers. SF 6 has been the subject of numerous electron attachment studies, and several authors have compared previous work [Chen et al, 1988;Christophorou, 1984;Petrovic and Crompton, 1985;Smith et al, 1984]. SF 6 is a fast attacher producing mainly (>99%) SF•-at 300 K, with a minor dissociative pathway forming SF•-+ F. Only the minor (i.e., slow) dissociative attachment pathway was considered in the study by Ravishankara et al [1993], and in the present treatment we assume that SF 6 is destroyed at the overall (fast) attachment rate in order to maximize the effects of electrons and arrive at a lifetime lower limit; this is discussed Table 1.…”
Section: Electronsmentioning
confidence: 73%
“…The presence of this peak suggests that the DEA reaction is thermoneutral or even slightly exothermic. Note that the threshold energy DE DEA = D 0 (SF 6 ) À EA ad (SF 5 ) for dissociative electron attachment of SF 6 + e À to SF À 5 þ Fð 2 P 3=2 Þ is not very well known (see, e.g., references in [3,18]; recent estimates gave DE DEA = 0.15 (15) eV [11,16]). The energy D 0 (SF 6 ) refers to dissociation of SF 6 (O h ) in its ground vibrational state into SF 5 in its ground vibrational state plus a separated F( 2 P 3/2 ) atom, and EA ad (SF 5 ) represents the adiabatic electron affinity of SF 5 with SF À 5 ðC 4v Þ in its vibrational ground state.…”
Section: Dependence Of Ir-enhanced Formation Of Sf à 5 On Electron Enmentioning
confidence: 97%
“…on the internal rovibrational energy of the SF 6 target molecules), exhibiting a shift and a rise of the peak cross section towards zero energy with increasing T G [3,8,15,[17][18][19]. To account for these observations, the higher energy peak in SF À 5 production has been attributed to attachment into a repulsive potential surface and subsequent direct dissociation [8,11,12,18]. Spence and Schulz [7], however, had found that the energy-integrated cross section for total anion formation at energies below 2 eV is independent of gas temperature from 300 to 1200 K. They postulated that there is a common electronic SF ÀÃ 6 complex initially formed and that the branching ratio for dissociation of this complex depends upon the thermal energy initially contained in the SF 6 molecule.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Subsequently, Jalbout et al . calculated AE a (SF 6 ): density functional, 1.6–3.0 eV; ab initio , 1.0–2.2 eV; semi‐empirical, 0.1–2.2 eV and D(SF 6 ), 4.0 eV; D(SF 5 ), 3.0 eV . Lobring and co‐workers cited E dea (SF 6 ), 0.12(2) and 0.45 eV and experimental and theoretical AE a : (eV) SF 6 , 1.0(2) to 3.22; SF 5 , 4.2 to 4.8; SF 4 , 1.5(2) to 2.62 .…”
mentioning
confidence: 99%